Characterizing memory requirements for queries over continuous data streams - Arasu, Arvind; Babcock, Brian; Babu, Shivnath; McAlister, Jon; Widom, Jennifer (ACM Transactions on Database Systems (TODS), 2004)
This article deals with continuous conjunctive queries with arithmetic comparisons and optional aggregation over multiple data streams. An algorithm is presented for determining whether or not any given query can be evaluated using a bounded amount of memory for all possible instances of the data streams. For queries that can be evaluated using bounded memory, an execution strategy based on constant-sized synopses of the data streams is proposed. For queries that cannot be evaluated using bounded memory, data stream scenarios are identified in which evaluating the queries requires memory linear in the size of the unbounded streams.